Integrating ex vivo drug sensitivity and genetic mutation analysis improves prediction of chemotherapy response in acute myeloid leukemia - Wěi Li; Min Ji; Wei Li; Ying Zhou; Ruinan Jia; Xin Wen; Shumin Jin; Yiping Hao; Min Dai; Shumei Xu; Qirui Zhou; Huihui Jiang; et al. (Functional & Integrative Genomics, 2026)

Arbuscular mycorrhizal fungi as a biological soil management practice for regulating soil carbon dynamics in agricultural soils: A global meta-analysis - Huawei Yang; Yuhang Zhang; Dingyi Liu; Yue Fan; Diwei Song; Pengju Li; Jingdan Yang; Xiaozhe Ma; Ruixin Bi; Shumin Li; Lingbo Meng (Soil and Tillage Research, 2026)

Non-destructive citrus freshness assessment by Raman spectroscopy exploiting oil and non-oil gland heterogeneity - Shumin Gao; Rongxuan Wu; Wen Zhang; Zhiqing Yang; Haofan Zhang; Min Chen; Shanjun Li (Postharvest Biology and Technology, 2026)

Decoding divergent degradation in single-phase 3R-AB4 and 2H-A5B19 superlattice hydrides for ultra-stable hydrogen storage - Hang Lu; Lixiang Ma; Kuiyue Wang; Qiuyue Jia; Lu Zhang; Yuan Li; Qiuming Peng; Shumin Han (Chemical Engineering Journal, 2026)

Subsidy pass-through and policy optimization for port drayage truck electrification under vehicle-leasing - Hongzhi Miao; Shumin Li; Xinwei Li; Jianfeng Zheng (Transportation Research Part D: Transport and Environment, 2026)

Spatiotemporal stratified flow analysis: A framework detecting associations between urban facilities and stratified human mobility patterns - Jianyu Li; Mingxing Hu; Shumin Wang; Ziye Liu; Jingyue Huang; Yueying Li; Fan Shi; Bing Han; Hui Wang (Journal of Transport Geography, 2026)

Cryogenic ultrasound-assisted ethyl acetate extraction enables selective defatting of egg yolk powder with enhanced phospholipid retention and functionality - Shumin Chen; Xiaoyun Liu; Mohamed Salama; Xiaomeng Li; Lingzhuo Li; Haoyang Sun; Lin Deng; Pengfei Geng; Zehao Wu; Wei Wu; Zhaoxia Cai (Food Research International, 2026)

Straw return regimes improve mollisol quality by reshaping microbial composition and metabolic profiles - Xinyuan Li; Yanhui Dou; Tingting Cui; Jing Xu; Yuxian Wang; Junqiang Wang; Rong Jiang; Shumin Sun; Guanghui Hu; Wanrong Gu (Applied Soil Ecology, 2026)

Ultimate removal of refractory organics in coking wastewater by integrated sustainable oxidation and adsorption processes - Yunxing Dong; Lili Zhang; Weihan Tian; Lele Gao; Shumin Li; Yingxin Gao; Min Yang (Journal of Environmental Sciences, 2026)

Constraints of trace elements of quartz on the origin of the Guanyintang antimony deposit, Western Hunan, South China - Junfeng Zhang; Huan Li; Shumin Chen; Majid Ghaderi; Weidong Ren; Annan Guan; Yue Hou (Journal of Asian Earth Sciences, 2026)

Interfacial and emulsifying properties of low-denatured soy protein prepared by self-coacervation - Shumin Zhang; Jiyang Cai; Zhuojia Lin; Chang Yang; Zhihong Lyu; Menghui Wang; Wentao Qian; Zhili Wan; Hongliang Li; Xiaoquan Yang (Food Hydrocolloids, 2026)

Structure-reactivity-transformation relationships of coal solvent-separated components during pyrolysis and carbonization: Role of inter-component coupling - Linhuan Wei; Shumin Shan; Shunxiang Lei; Weichao Li; Dailin Zhang; Zenglan Zhang; Weidong Zhang; Zhiping Lei; Hengfu Shui; Jingchong Yan (Chemical Engineering Journal, 2026)

Breaking the irreversibility barrier: Redox-enabled regeneration of oxygen vacancies in mixed metal oxides through quenching-mediated reductive reconstruction - Fengjiao Zhou; Can Peng; Shumin Liu; Xingyou Zhou; Yuekai Hu; Aihua Xu; Xiuying Liu; Shuaiqi Zhao; Xiaoxia Li (Chemical Engineering Journal, 2026)

Diurnal variations of organic molecules in atmospheric PM2.5 in urban areas of the Yangtze River Basin, China characterized by UHPLC–Orbitrap MS - Xin Ou; Lijuan Li; Xin Qi; Jiawei Zhou; Hanxiong Che; Zhier Bao; Yiliang Liu; Lingshuo Meng; Xin Long; Xiaojiang Yao; Shumin Zhang; Yang Chen (Atmospheric Environment, 2026)

Parameter Optimization of Coal Seam Hydraulic Seepage Enhancement Measures Based on Principal Component Analysis - Xuelong Li; Ruihao Han; Shumin Liu; Baolin Li; Ni Wan (Rock Mechanics and Rock Engineering, 2026)

The role of artificial intelligence in equine colic: A scoping review of diagnostic, prognostic, and decision-support applications - Yu Gao; Zijun Luo; Zhixiang Dong; Shumin Li (The Veterinary Journal, 2026)

Threshold responses of diatom community to hydrological changes in an alpine peatland based on long-term (2014–2020) monitoring data - Xu Chen; Junlu Li; Jia Peng; Shuangyu Xu; Jun He; Shumin Qiao; Linghan Zeng; Xianyu Huang (Journal of Hydrology, 2026)

Impacts of processing and environmental factors on fucoxanthin from brown algae: structural stability, bioactivity, and underlying molecular mechanisms - Shumin Cai; Mingrui Ma; Jialin Li; Yingying Zhao; Yimeng Ren; Dandan Ren; Yunhai He; Yidi Cai; Shu Liu; Qiukuan Wang; Yichao Ma (Food Chemistry, 2026)

Mechanisms of water-state transition and hydrophobicity evolution of organics during ultrasonic dewatering of algal sludge - Shumin Yang; Li-an Hou; Rongsheng Ning; Xinyuan Yi; Shuili Yu; Yulin Tang (Environmental Research, 2026)

Effects of Antioxidant DI-3-N-Butylphthalide on Hemorrhagic Transformation Assessed by Propensity Score Matching in a Real-World Thrombolyzed Ischemic Stroke Patient Setting - Ziqi Han; He Liang; Tieping Fan; Mario Minor Murakami Junior; Shumin Li; Ruikang Sun; Daoyong Peng; Shiwei Du; Yu Hasegawa; Haojie Gao; Dong Chen; Dirk M. Hermann; et al. (Translational Stroke Research, 2026)

Decadal evolution and dynamics of the Longxigou landslide’s composite deforming surface revealed by space-air-ground investigation strategy - Shumin Feng; Keren Dai; Zhiyu Li; Peng Zeng; Weiwei Tian; Xiquan Wang; Yanfei Kang; Hong Xu; Lichuan Chen (Landslides, 2026)

PLX3397 Reshapes Hepatic Lipid Metabolism Independent of Microglial Depletion - Jiahui Lyu; Wang Cheng; Chun-Yue Li; Jiayan Wang; Xiaorong Zhang; Huifang Lou; Yalin Hu; Zhihua Gao; Shumin Duan; Kelei Cao (Neuroscience Bulletin, 2026)
Colony-stimulating factor 1 receptor (CSF1R) inhibitors, such as PLX5622 and PLX3397 (pexidartinib), are widely used for in vivo microglial depletion and for investigating microglial functions and therapeutic potential. Although CSF1R inhibitor-based studies have uncovered important roles for microglia in processes, such as anesthesia, addiction, and obesity, whether the resulting phenotypes reflect microglial depletion alone remains increasingly debated. Our previous work has shown that PLX5622 activates hepatic constitutive androstane receptor (CAR)-dependent xenobiotic metabolism, altering the metabolism of anesthetics and addictive drugs, and amplifying apparent microglial phenotypes. Whether other CSF1R inhibitors, particularly the FDA-approved PLX3397, exert systemic metabolic effects that may influence the interpretation of brain phenotypes remains unknown. Here, we demonstrate that PLX3397 exerts hepatic metabolic effects that are mechanistically distinct from those induced by PLX5622. Although PLX3397 only weakly affects xenobiotic metabolism, it markedly enhances endogenous hepatic lipid metabolism, inducing a fasting-like state characterized by increased lipid utilization and ketogenesis despite the absence of nutrient deprivation. By uncovering previously unrecognized peripheral effects of PLX3397, our findings identify brain-periphery interactions as a potential source of confounding in studies of microglial function. These results suggest that systemic metabolic effects should be carefully considered when interpreting neural or behavioral phenotypes in pharmacological microglia depletion paradigms.

β-Sitosterol: a Common Compound in Hundreds of Traditional Chinese Medicine Treatments for Infertility and its Effects on Human Ovarian Granulosa Cells - Yu Sun; Gengchen Feng; Ziyi Yang; Yimeng Li; Shumin Li; Shigang Zhao (Phenomics, 2026)

Construction of Pt-TiOx interfacial sites via Pt-TiO2 metal-support interaction for efficient catalytic dehydrogenation of methylcyclohexane - Zhengjian Li; Mingzhi Wang; Shumin Liu; Huayue Yang; Yun Zhao; Lin Gu; Guangxu Chen (Science Bulletin, 2026)

Nitrogen limitation enhances Irgarol 1051 toxicity by aggravating PSII photoinhibition in the marine diatom Thalassiosira weissflogii - Yuheng An; Shumin Zeng; Futian Li; Jun Wang; Xuexia Zhu; Juntian Xu; Yaping Wu (Marine Environmental Research, 2026)

Highland Barley's future: Processing innovation empowers emerging opportunities in global health foods and sustainable agriculture - Xinlai Dou; Luman Sang; Liangxing Zhao; Yiqing Zhu; Shumin Shu; Yan Zhang; Jing Ou; Hongying Hua; Ge Li; Yong Xue; Qingyu Zhao; Chao Wang; et al. (Trends in Food Science & Technology, 2026)

Fluid source and evolutionary processes of the Jinkeng and Huanggou gold deposits, southwestern Hunan, South China: Constraints from pyrite and arsenopyrite chemistry and quartz HO isotopes - Xiaofeng Li; Huan Li; Yue Hou; Ruilin Wang; Majid Ghaderi; Zhekai Zhou; Chunhua Wen; Shumin Chen (Geochemistry, 2026)

NiV-OH/CoNi-MOF heterostructures enabling intercalation–phase transition synergy for high-energy asymmetric supercapacitors - Yina Xiang; Shumin Qin; Shuang Luo; Hui Zhou; Guochuang Tian; Feng Zhan; Jien Li (Chemical Engineering Journal, 2026)

Enhancement of the gas/water interfacial properties of heat-induced α-lactalbumin via inhibiting the thermal aggregation: impacts of gypenoside concentrations - Shumin Guo; Zhishen Mu; Xin Wen; Hongyu Li; Zhanmei Jiang; Yun Chen (Food Hydrocolloids, 2026)

Mechanisms of flavonoid-mediated amelioration of MASLD: flavonoids, their metabolites or impact on gut microbes? - Ruxuan Chen; Xionghui Wu; Ning Yin; Enjun Xie; Shumin Sun; Jie Shen; Yunmei Chen; Fenghua Zhou; Tao Li; Qili Li; Donglin Su; Fuhua Fu; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Effective degradation of aflatoxin B1 and zearalenone by a recombinant laccase from Heyndrickxia shackletonii - Fred Mwabulili; Peng Li; Qian Li; Shumin Sun; Yuhui Yang; Weibin Ma; Xiao Li; Hang Jia; Yanli Xie (World Journal of Microbiology and Biotechnology, 2026)

From molecular adsorption to process design: selective flotation of bastnaesite and monazite with phthalic acid as collector - Maoyuan Wang; Wenbo Li; Yuexin Han; Xiaolong Zhang; Shumin Zhang (Minerals Engineering, 2026)

Synergistic coupling of ultrasonic activation and BaTiO3 piezoelectric ceramic membranes for robust algae-water separation: Dynamics of foulant migration and radical oxidation - Shumin Yang; Li-an Hou; Xinyuan Yi; Yongjie Huang; Qianli Zhang; Shuili Yu; Yulin Tang (Journal of Environmental Chemical Engineering, 2026)

Effects of photochemical and aqueous-phase oxidation on secondary formation during the 31st FISU Summer World University Games, 2023 - Xiaoling Zeng; Zhier Bao; Jiawei Zhou; Guangming Shi; Li Zhou; Shumin Zhang; Xin Qi; Keding Lu; Chongzhi Zhai; Zhenliang Li; Xin Li; Chao Peng; et al. (Journal of Environmental Sciences, 2026)

Tuning surface residual lithium into a Li-ion-conductive protective interphase toward stable Ni-rich cathodes - Shumin Liu; Huangzhang Zhou; Wenhao Jia; Yingjie Sun; Peng Gao; Ruichen Zhu; Yongming Zhu; Xudong Li; Liguang Wang (Chemical Engineering Journal, 2026)

Fine-mapping and candidate gene analysis of qFF3.1 conferring fruit firmness in a modern tomato variety - Yunhao Han; Xin Li; Can Zhu; Yonglian Wang; Junling Hu; Shumin He; Saifeng Guo; Xiaoxiao Lu; Chunyang Pan; Zejun Huang; Yanmei Guo; Xiaoxuan Wang; et al. (Theoretical and Applied Genetics, 2026)

Dynamic modulation of severe Typhoon Son-Tinh’s (2012) inner-core vorticity structure during rapid intensification: terrain-induced impacts over Hainan Island​ - Shumin Chen; Mingsen Zhou; Weibiao Li (Natural Hazards, 2026)

IL-37 attenuates HEI-OC1 cell senescence by modulating the NF-κB pathway - Luan Xu; Beibei Xu; Liya Ding; Shumin Li; Xiaopei Wu; Guanghui Wang; Yuefeng Han (Molecular & Cellular Toxicology, 2026)

Conserved region amino acid mutations in Calcin: Altering the RyR structural-functional relationship - Lianbo Wang; Xiaoyu Hua; Xiaofen Ma; Jianguo Wang; Li Xiao; Shumin Wang; Hao Liu; Yangfei Zhao; Héctor H. Valdivia; Liang Xiao; Jinming Wang (Toxicon, 2026)

Thermoresponsive gamma-cyclodextrin-based porous composite functionalized with N-isopropylacrylamide and soybean hull polysaccharide for controlled curcumin delivery - Shumin Wang; Shengnan Wang; Ziyang Zhang; Jun Li; He Liu; Chunlei Liu (Journal of Food Engineering, 2026)

Biodegradation of 2,4-di-tert-butylphenol in continuous cropping field: Impacts on sustainable cultivation of Lilium brownii - Shumin Zhong; Longzhu Tang; Lu Su; Deyuan Chen; Xuwei Li; Li Shi; Xiaogang Li; Xiaolan Liao (Journal of Environmental Management, 2026)

Characterization of bitter peptide release and antioxidant activity of peptide mixture of clam (Aloididae aloidi): Combining sensory and physicochemical approach - Beibei Ye; Yilin Wang; Fengchun Liu; Zhengpeng Wei; Cikun Liu; Shumin Yi; Xuepeng Li; Jianrong Li (Food Bioscience, 2026)

The role of transition metal Y, Ti, and Zr substitutions on the hydrogen storage of Ce2Ni7-type Sm–Mg–Ni-based superlattice alloys - Lian Cong; Zhuohan Zhang; Kuiyue Wang; Yuan Li; Qiuming Peng; Lu Zhang; Shumin Han (Chemical Engineering Journal, 2026)

Beyond urban hierarchy: unveiling the spatial patterns of nonhierarchical carbon emissions - Jianyu Li; Mingxing Hu; Shumin Wang; Ziye Liu; Jingyue Huang (Sustainable Cities and Society, 2026)

RSM-based development and optimization of a novel fracture sealing material for secondary grouting in extraction boreholes - Junxiang Zhang; Yijian Guo; Bo Li; Yadong Bian; Shumin Ding; Lina Qu; Zhenfeng Wang; Yaocai Tang; Pan Chen (Fuel, 2026)

Development of Salmon bone steak protein-based emulsion gels: Effects of fish oil volume fraction on gelation and structural properties - Yuting Wang; Hanyue Wang; Honglei Zhao; Yongxia Xu; Shumin Yi; Xuepeng Li; Jianrong Li (Food Chemistry, 2026)

The promoter sequence of (-)-limonene synthase in Mentha Canadensis and its strong activity in the glandular trichome and in the stomatal guard cells - Shumin Li; Zhichao Xue; Taolan Xiao; Xiwu Qi; Hailing Fang; Li Li; Yang Bai; Dongmei Liu; Qun Liu; Zequn Chen; Xu Yu; Chengyuan Liang (Acta Physiologiae Plantarum, 2026)

The immunosuppressive receptor FcγRIIb (CD32b) gets involved in immune response of Nile Tilapia (Oreochromis niloticus) against bacterial infection - Jiadong Li; Shumin Du; Qingliang Zeng; Zhanyao Lin; Yansong Wang; Lu Deng; Xiaoxue Yin; Yanjian Yang; Zheng Guo; LiangLiang Mu; Jianmin Ye (Aquaculture, 2026)

Prevalence, migration and exposure assessment of bisphenol compounds in pre-cooked foods - Shumin Liang; Chen Lan; Wenxiu Wang; Shuai Wu; Liying Zhang; Ruosi Li; Jing Zhan; Jiaying Liu (Journal of Hazardous Materials, 2026)

Enhanced effect and mechanism of biochar on the nitrogen removal of low C/N wastewater by cold-tolerant heterotrophic nitrifying–aerobic denitrifying bacterium - Xiaoyu Li; Meizhen Tang; Jie Jiang; Shiqiang Ma; Shumin Yao; Yuewei Yang (Journal of Contaminant Hydrology, 2026)

Trio-amine blends combined with fly ash-catalyzed desorption: A synergistic approach for energy-efficient CO2 capture - Rui Zhang; Qingzhi Zhang; Lianghong Zhou; Jiaqi Qu; Shumin Ouyang; Minyue Hu; Shiying Zou; Chao’en Li; Francesco Barzagli (Fuel, 2026)

Synergistic effect of H2 and coal thermal dissolution solubles on the microstructure and dissolution loss performance of coke - Shumin Shan; Kaixiang Ma; Baoguo Wu; Jingchong Yan; Zhanku Li; Weidong Zhang; Zhicai Wang; Zhiping Lei; Shibiao Ren; Hengfu Shui (Chemical Engineering Journal, 2026)

Environmental interactions drive soil organic and inorganic carbon distributions in Southeast China’s mangrove restoration areas - Shuya Xie; Xianglan Li; Zhe Xu; Zhongpeng Ma; Zhao Zhang; Shumin Zhang; Yahui Chen; Minghai Xu; Wei Chen; Sheng Yang; Qiuxia Chen; Xing Liu (CATENA, 2026)

Spatially-confined bubble plasma oxidation induced by microchannel discharge to boost energy efficiency in water treatment - Shumin Li; Bangdou Huang; Yingxin Gao; Yunxing Dong; Qi Wang; Lili Zhang; Cheng Zhang; Jianwei Yu; Min Yang (Water Research, 2025)

Synergistic KOH/MgSO₄ activation of hazelnut shell biochar: Tailored hierarchical porosity and surface chemistry boosting high-efficiency capacitive deionization - Shumin He; Youzhao Wang; Xiaolong Gao; Jiedong Hao; Enbo Zhang; Rui Du; Tengfei Li; Yaonan Zhu; Tong Zhu (Journal of Environmental Chemical Engineering, 2025)

Construction of NH2-ZIF-7/g-C3N4/Pebax mixed matrix membranes with heterostructures for flue gas decarbonization - Suyue Zhong; Shumin Li; Wenjun Su; Zeyang Di; Weimin Liu; Jian Li (Chemical Engineering Journal, 2025)

Dual-functional Nb/Sm3H7 interface for enhanced hydrogen storage performance in Mg/MgH2 system - Zhuohan Zhang; Zhichao Yu; Zhaoyang Liu; Lixiang Ma; Jing Wang; Yuan Li; Lu Zhang; Shumin Han (Chemical Engineering Journal, 2025)

Enhanced dehydrogenation kinetics and cyclic stability of NaAlH4 through nitrogen coupling with Ti3C2 MXene - Zhenluo Yuan; Ruyi Guo; Xiuxiu Zhang; Jiabao Cai; Haiwen Li; Qiuming Peng; Shumin Han; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2025)

WDGBANDTI: A Deep Graph Convolutional Network-Based Bilinear Attention Network for Drug-Target Interaction Prediction with Domain Adaptation - Nianrui Wang; Shumin Zhao; Ziwei Li; Jianqiang Sun; Ming Yi (Interdisciplinary Sciences: Computational Life Sciences, 2025)

From iron concentrate to clean steel: A green short-process production technology centered on preparing high-purity iron concentrate - Wencheng Ge; Jie Liu; Tianjiao Chang; Yanjun Li; Yongsheng Sun; Shumin Zhang; Yuexin Han; Yimin Zhu (Minerals Engineering, 2025)

Bile acids and apical sodium-dependent bile acid transporter impact per- and polyfluoroalkyl substances absorption: Evidence from in vivo and cross-sectional studies - Yiran Liang; Jing Zhan; Xiao Liu; Shumin Liang; Ruosi Li; Yinchuan Lv; Jingjing He; Jiaying Liu (Journal of Hazardous Materials, 2025)

pH-responsive microgels constructed from soy protein coacervates: Structure and rheology at the oil-water interface - Jiyang Cai; Shumin Zhang; Sili Liu; Xiang Li; Zhili Wan; Boris A. Noskov; Xiaoquan Yang (Food Hydrocolloids, 2025)

Porous manganese-based ion sieve for sustainable lithium extraction from brine: High-efficiency adsorption and rapid kinetics - Yu Dai; Xiaotian Zhang; Jing Sun; Shumin Wu; Zhongwei Zhao; Wenhua Xu; Guoxing Ren; Yongli Li; Dongfu Liu (Desalination, 2025)

Chitosan/PVA nanofibrous membrane loaded with cerium manganese nanoparticles/SNAP promotes wound healing in diabetes - Zhonghao Jiang; Zhuo Yan; Shumin Yan; Zihao Chen; Lianhai Li; Guoliang Huang; Li Li; Jiantao Lin (Chemical Engineering Journal, 2025)

Experimental study on the crack propagation characteristics of drilled-slit and grouted rock samples based on CT three-dimensional scanning - Jianhua Fu; Xuelong Li; Hengjie Qin; Shuailin Wang; Shumin Liu; Zhiming Wang; Zeqi Wu; Zhen Lou (Process Safety and Environmental Protection, 2025)

Vegetation-hydrology coupling drives spatiotemporal dynamics of soil organic carbon sequestration in the northernmost restored mangrove areas in southern China - Shuya XIE; Xianglan LI; Meijie ZHU; Yang GUO; Zhao ZHANG; Shumin ZHANG; Yahui CHEN; Zhe XU; Pengpeng TIAN; Yuting HUANG; Churui GUAN (Pedosphere, 2025)

Macrophage cytoskeletal and immune responses to photoaged and gastrointestinal-transformed polylactic acid micro/nanoplastics with protein corona - Xuri Wu; Feng Tan; Han Zhang; Liping Huang; Yan Wang; Xin He; Rui Cai; Shumin Li (Journal of Hazardous Materials, 2025)

Polysaccharide emulsion gels for dysphagia-friendly surimi-based diets: development and application - Miaoyuan Li; Qinheng Ji; Zhaoran Cai; Shumin Zhang; Jiaxin Shao; Weina Cai; Hongmei Liao (Food Research International, 2025)

Unveiling the intrinsic electrochemical properties and stability of phase-pure A5B19 La–Mg–Ni-based superlattice allotropes - Kuiyue Wang; Anyi Zhang; Ning Zhang; Wenfeng Wang; Shumin Han; Qiuming Peng; Yuan Li; Lu Zhang (Chemical Engineering Journal, 2025)

High-capacity superlattice La0.55Sm0.20Mg0.25Ni3.27Al0.01 hydrogen storage alloys with series of (A7B23) -(A2B7)1- (x = 0, 0.1, 0.9) structures for nickel-metal hydride batteries - Ning Zhang; Beichen Zhao; Wenfeng Wang; Anyi Zhang; Qiuyue Jia; Yuan Li; Lu Jian; Tianzi Li; Shumin Han; Lu Zhang (Chemical Engineering Journal, 2025)

Incorporating frequency domain features into radiomics for improved prognosis of esophageal cancer - Shu Chen; Shumin Zhou; Liyang Wu; Shuchao Chen; Shanshan Liu; Haojiang Li; Guangying Ruan; Lizhi Liu; Hongbo Chen (Medical & Biological Engineering & Computing, 2025)

Enhanced winter performance of constructed wetlands via biochar-immobilized Psychrotrophic bacteria - Xiaoyu Li; Meizhen Tang; Shumin Yao; Shiqiang Ma; Yuewei Yang (Journal of Water Process Engineering, 2025)

Hierarchical Al-CoP/Ni2P heterostructure for alkaline hydrogen evolution reaction - Kangli Chen; Zhichao Yu; Yuan Li; Wenfeng Wang; Lu Zhang; Shumin Han (Fuel, 2025)

The legal and socioeconomic challenges for environmental protection in marine policy and the silk route maritime - Muhammad Bilawal Khaskheli; Yincheng Li; Yongchen Zhao; Wang Shumin (Frontiers in Marine Science, 2025)
Introduction The intersection of legal frameworks and socioeconomic interests poses a significant challenge to ocean policy focused on environmental protection. This article examines the complexities of international regulation, national interests, and local needs. Legal frameworks like the United Nations Convention on the Law of the Sea provide a foundation for sustainable use and environmental protection. However, the implementation of these frameworks varies significantly around the world. Socioeconomic disparities and their impact on governance and resource management further undermine resource utilization and contribute to environmental degradation. The research compares and contrasts the environmental laws of various countries and examines the laws of nations under the United Nations’ global governance. Methods This paper’s research approach adopts a literature review with secondary data from official databases, such as UNCLOS, the United Nations, and other official databases. We also utilize the consequences of recently published papers in high-impact publishers such as Frontiers, Oxford University Press, Springer, Elsevier, IEEE, Wiley, Taylor & Francis, and MDPI. For cross-border cooperation, there are possibilities and pitfalls of harmonizing monitoring and enforcement of policy. Results It has six tables and three figures that provide statistics reflecting global performance in marine and environmental law, designed to protect the world. Discussion Therefore, the Belt and Road Initiative and the China-Pakistan Economic Corridor must tackle these issues through collaborative efforts that engage coastal governance participation. Effective ocean governance within these frameworks can encourage regional cooperation, ensuring legal commitments align with socioeconomic realities. Ultimately, it is crucial to maintain a balance that supports marine conservation and sustainable development. Adaptive management strategies and institutional collaboration are needed to pursue these complexities, develop sustainability and resilience in marine ecosystems, and inform more effective environmental protection policies.

Germline-specific deletion of testis-highly expressed Lrwd1 reveals nonessential roles in male fertility - Chunhai Luo; Dalin Liu; Ziqi Yu; Zhiwei Fan; Haoran Xu; Shumin Zhou; Xuanjing Zhu; Hanchao Liu; Lifu Shao; Yunhao Wu; Zhean Li; Fei Sun; et al. (Theriogenology, 2025)

An interpretable spatially weighted machine learning approach for revealing spatial nonstationarity impacts of the built environment on air pollution - Shumin Wang; Mingxing Hu; Jianyu Li; Guoao Liu; Wanqi Hu; Junheng Qi; Jingyue Huang; Ziye Liu; Hui Wang; Bing Han (Building and Environment, 2025)

Promotion of maize straw degradation rate by altering microbial community structure through the addition of soybean straw - Xiaodan Liu; Hongrui Huo; Yuhang Zhang; Huawei Yang; Shumin Li; Lingbo Meng (Plant and Soil, 2025)

Eutrophication mitigates Cu-induced inhibition on growth and photosynthetic performance in the marine diatom Thalassiosira weissflogii - Shumin Zeng; Xiangyu Li; Linrong Peng; Juntian Xu; Zhenzhen Li; Yaping Wu (Marine Pollution Bulletin, 2025)

Inferring diapycnal mixing using the internal wave continuum from the high resolution ocean model - Shumin Jiang; Dejun Dai; Dingqi Wang; Shihong Wang; Ying Li; Jingsong Guo; Fangli Qiao (Ocean Modelling, 2025)

Improving the gel properties of Nemipterus virgatus myosin gel using soy protein isolate-stabilized Pickering emulsion - Shouyu Feng; Cikun Liu; Yanwei Liu; Shumin Yi; Jianrong Li; Bin Zhang; Xuepeng Li (Food Chemistry, 2025)

The CPDG treatment and dose-dependent effects of zein-stevioside conjugates on formation, drainage behavior, and interfacial structure of Pickering foam - Zihan Qu; Tongliang Yang; Yushan Wang; Shumin Zhang; Zhili Wan; Shuhong Li; Ye Chen; Guiyun Chen (Food Chemistry, 2025)

Improvement of finescale parameterization through reducing uncertainty in spectrum estimation - Shumin Jiang; Dejun Dai; Dingqi Wang; Jia Deng; Jia Sun; Ying Li; Jingsong Guo; Fangli Qiao (Dynamics of Atmospheres and Oceans, 2025)

Improvement of the rheological properties and freeze-thawing stability of Pickering emulsions filled emulsified surimi gels:Effects of the interfaces of surimi particles and konjac glucomannan - Cikun Liu; Beibei Ye; Shumin Yi; Xuepeng Li; Yanshun Xu; Wenshui Xia (Food Hydrocolloids, 2025)

Vacancy engineering in transition metal selenides for long-lasting and fast-charging Na-ion batteries - Changsheng An; Jialing Liu; Chen Xu; Chi Zhang; Ruiting Li; Shumin Zhang; Shiying Zhang; Jinbo Li; Chao Cai; Xing Ou (Chemical Engineering Journal, 2025)

Strategic design of high-directional scaffold enabling accelerated kinetics for high-loading low-temperature lithium-sulfur batteries - Junye Shi; Chenxi Yu; Yuchen Ning; Bao Li; Bao Wang; Shumin Zheng (Chemical Engineering Journal, 2025)

Risks of respiratory and circulatory system diseases induced by exposure to PM2.5 in high humidity and low solar radiation environments: disease types, genes, and functions - Xiaomeng Li; Liru Zhang; Zhengliang Zhang; Xuan Li; Jingli Qian; Jiawei Zhou; Hanxiong Che; Yan Han; Xin Qi; Fumo Yang; Yu Huang; Chao Peng; et al. (Environmental Geochemistry and Health, 2025)

Distributed predefined-time robust adaptive control design for attitude consensus of multiple spacecraft - Qijia Yao; Qing Li; Shumin Xie; Hadi Jahanshahi (Advances in Space Research, 2025)

Patterns and drivers of soil autotrophic nitrification and associated N2O emissions - Shumin Guo; Roland Bol; Zhutao Li; Jie Wu; Haiyan Lin; Xiaomeng Bo; Zhiwei Zhang; Zhaoqiang Han; Jinyang Wang; Jianwen Zou (Soil Biology and Biochemistry, 2025)

Ultra-fast preparing carbon nanotube-supported Ni-Fe bimetallic compounds as robust electrocatalysts for oxygen evolution reaction - Taotao Gao; Qi An; Shumin Yu; Xiangrui Feng; Bing Li; Yanyan Huang; Hai Lan; Dan Xiao (Fuel, 2025)

Degradation of AFB1 in edible oil by aptamer-modified TiO2 composite photocatalytic materials: Selective efficiency, degradation mechanism and toxicity - Mengdan Ku; Jiajun Li; Wenhao Zhang; Shumin Sun; Yaqi Zhang; Yanli Xie (Food Chemistry, 2025)

Correlation between pollen morphology, karyotype, floral pigments, and scent components and morphological classification of 15 species and hybrids of Syringa L - Feng Qian; Xiaoou Zhai; Ziyin Cheng; Zhenyu Yu; Guoqiang Chen; Yan Gao; Liwei Sun; Li Fang; Shumin Yang; Shaoqi Xu; Huimin Liu (The Science of Nature, 2025)

The Paraventricular Hypothalamus: A Sorting Center for Visceral and Somatic Pain - Li Sun; Shumin Duan (Neuroscience Bulletin, 2025)

An electrically activable nanochip to intensify gas-ionic-immunotherapy - Gang Wang; Jingrui Li; Shumin Sun; Yuqi Yang; Zhihui Han; Zifan Pei; Liang Cheng (Science Bulletin, 2025)

Long-term effects of Nε-carboxymethyllysine intake on intestinal barrier permeability: Associations with gut microbiota and bile acids - Xin Qiang; Xiaoyuan Wang; Shumin Liang; Shaogang Li; Yinchuan Lv; Jing Zhan (Food Research International, 2025)

Expression, characterization, and application of an aldo-keto reductase mined from Bacillus velezensis Vel-HNGD-F2 for deoxynivalenol biodegradation - Junxia Liu; Peng Li; Xiao Li; Yanli Xie; Fred Mwabulili; Shumin Sun; Yuhui Yang; Weibin Ma; Qian Li; Hang Jia (Food and Chemical Toxicology, 2025)

An in-depth understanding of the role and mechanisms of T cells in immune organ aging and age-related diseases - Yudai Xu; Zijian Wang; Shumin Li; Jun Su; Lijuan Gao; Junwen Ou; Zhanyi Lin; Oscar Junhong Luo; Chanchan Xiao; Guobing Chen (Science China Life Sciences, 2025)

Tidal currents and atmospheric inorganic nitrogen contribute to diurnal variation of dissolved nutrients and chlorophyll a concentrations in Mirs Bay, Hong Kong - Ho Wen Lo; Xu Yu; Hanzhe Chen; Wai Ching Chu; Nga Man Chung; Sze Wing Lau; Jinjian Li; Shumin Liang; Kezheng Liao; Henry Charles James Thomas; Ziyan Wang; Zijing Zhang; et al. (Regional Studies in Marine Science, 2025)

Interdecadal variability and possible drivers of summer extreme precipitation on the low latitude plateau of southwestern China - Yan Jin; Yunxia Wan; Huahong Li; Chaoyong Tu; Hongming Yan; Yunsha Hai; Huigeng He; Shumin Chen; Min Xie (Theoretical and Applied Climatology, 2025)

Factors influencing the dissolution rate of radon gas in water - Xiongjie Zhang; Li Feng; Ye Zhang; Yangyang Feng; Bao Wang; Haixian Zhou; Shumin Zhou (Journal of Environmental Radioactivity, 2024)

Lung cell injury risks of PM2.5 exposure in the high humidity and low solar radiation environment of southwestern China - Qin Zhang; Xuan Li; Xiaomeng Li; Ronghua Zhang; Bi Ren; Hanxiong Che; Xin Qi; Jiawei Zhou; Jiancai Tang; Andre S.H. Prevot; Zhenzhong Liu; Li Jiang; et al. (Atmospheric Environment, 2024)

Vitamin C ameliorates D-galactose-induced senescence in HEI-OC1 cells by inhibiting the ROS/NF-κB pathway - Beibei Xu; Guanghui Wang; Luan Xu; Liya Ding; Shumin Li; Yuefeng Han (Molecular Biology Reports, 2024)

Performance Characteristics of Newly Developed Real-Time Wave Measurement Buoy Using the Variometric Approach - Chen Xue; Jingsong Guo; Shumin Jiang; Yanfeng Wang; Yanliang Guo; Jie Li (Journal of Marine Science and Engineering, 2024)
Accurate measurement of ocean wave parameters is critical for applications including ocean modeling, coastal engineering, and disaster management. This article introduces a novel global navigation satellite system (GNSS) drifting buoy for surface wave measurements that addresses the challenges of performing real-time, high-precision measurements and realizing cost-effective large-scale deployment. Unlike traditional approaches, this buoy uses the kinematic extension of the variometric approach for displacement analysis stand-alone engine (Kin-VADASE) velocity measurement method, thus eliminating the need for additional high-precision measurement units and an expensive complement of satellite orbital products. Through testing in the South China Sea and Laoshan Bay, the results showed good consistency in significant wave height and main wave direction between the novel buoy and a Datawell DWR-G4, even under mild wind and wave conditions. However, wave mean period disparities were observed partially because of sampling frequency differences. To validate this idea, we used Joint North Sea Wave Project (Jonswap) spectral waves as input signals, the bias characteristics of the mean periods of the spectral calculations were compared under conditions of identical input signals and gradient-distributed wind speeds. Results showed an average difference of 0.28 s between the sampling frequencies of 1.28 Hz and 5 Hz. The consequence that high-frequency signals have considerable effects on the mean wave period calculations indicates the necessity of the buoy’s high-frequency operation mode. This GNSS drifting buoy offers a cost-effective, globally deployable solution for ocean wave measurement. Its potential for large-scale networked ocean wave observation makes it a valuable oceanic research and monitoring instrument.

Deformation characteristics of root-reinforced soil under traffic induced cyclic loading - Shusen Liu; Jun Li; Shumin Lyu; Yi Fang; Xiaodong JI; Junjun Ni (Transportation Geotechnics, 2024)

Research diversity and advances in simultaneous removal of multi-mycotoxin - Fred Mwabulili; Peng Li; Jinghao Shi; Hongxin Zhang; Yanli Xie; Weibin Ma; Shumin Sun; Yuhui Yang; Qian Li; Xiao Li; Hang Jia (Toxicon, 2024)

Perfluorooctanoic acid (PFOA) and its alternative perfluorobutanoic acid (PFBA) alter hepatic bile acid profiles via different pathways - Xiaoyuan Wang; Yinchuan Lv; Xin Qiang; Shumin Liang; Ruosi Li; Jing Zhan; Jiaying Liu (Science of The Total Environment, 2024)

Leak detection in water supply pipeline with small-size leakage using deep learning networks - Pengcheng Guo; Shumin Zheng; Jianguo Yan; Yan Xu; Jiang Li; Jinyang Ma; Shuaihui Sun (Process Safety and Environmental Protection, 2024)

Transcriptional regulation and functional validation analysis of the McbZIP1 in Mentha canadensis L. - Xu Yu; Shumin Li; Taolan Xiao; Xiwu Qi; Hailing Fang; Li Li; Yang Bai; Dongmei Liu; Qun Liu; Zequn Chen; Zhichao Xue; Chengyuan Liang (Plant Science, 2024)

Identification of the effects of low temperature on grain-setting rate of different types of late-season rice (Oryza sativa) during heading - Yibo Gao; Yi Li; Ling Huang; Jinsong Zhao; Shumin Li; Jianxin Lu; Xinghua Li; Tewu Yang (Field Crops Research, 2024)

Flexible and Flame Retardant Cotton Fiber-reinforced CS/CNF/EP Composites For a Sensitive Fire Warning - Yi Xu; Shilong Liu; Shumin Xu; Gao Liu; Gehui Li (Chemical Engineering Journal, 2024)

Structural design of hierarchical porous biomass carbon with a built-in electric field for efficient peroxymonosulfate activation - Xue Gao; Bin Wang; Jinyuan Liu; Xingwang Zhu; Xianglin Zhu; Shumin Zhu; Chao Huang; Qingdong Ruan; Dan Li; Liangliang Liu; Huaming Li; Hui Xu; et al. (Chemical Engineering Journal, 2024)

Special Issue Celebrating the 25th Anniversary of the Institute of Neuroscience, CAS - Ting Lv; Yefei Li; Fei Dong; Shumin Duan (Neuroscience Bulletin, 2024)

Nucleus Accumbens Corticotropin-Releasing Hormone Neurons Projecting to the Bed Nucleus of the Stria Terminalis Promote Wakefulness and Positive Affective State - Gaojie Pan; Bing Zhao; Mutian Zhang; Yanan Guo; Yuhua Yan; Dan Dai; Xiaoxi Zhang; Hui Yang; Jinfei Ni; Zhili Huang; Xia Li; Shumin Duan (Neuroscience Bulletin, 2024)
The nucleus accumbens (NAc) plays an important role in various emotional and motivational behaviors that rely on heightened wakefulness. However, the neural mechanisms underlying the relationship between arousal and emotion regulation in NAc remain unclear. Here, we investigated the roles of a specific subset of inhibitory corticotropin-releasing hormone neurons in the NAc (NAc CRH ) in regulating arousal and emotional behaviors in mice. We found an increased activity of NAc CRH neurons during wakefulness and rewarding stimulation. Activation of NAc CRH neurons converts NREM or REM sleep to wakefulness, while inhibition of these neurons attenuates wakefulness. Remarkably, activation of NAc CRH neurons induces a place preference response (PPR) and decreased basal anxiety level, whereas their inactivation induces a place aversion response and anxious state. NAc CRH neurons are identified as the major NAc projection neurons to the bed nucleus of the stria terminalis (BNST). Furthermore, activation of the NAc CRH -BNST pathway similarly induced wakefulness and positive emotional behaviors. Taken together, we identified a basal forebrain CRH pathway that promotes the arousal associated with positive affective states.

Thermal aggregation behavior of silver carp myofibrillar protein at low salt content: Effect of oat β-glucan combined with ultrasound-assisted heating - Honglei Zhao; Xueli He; Yanan Lv; Yongxia Xu; Shumin Yi; Jianrong Li; Xuepeng Li (Food Chemistry, 2024)

Development of a NiFe2O4 covalent organic framework based magnetic solid-phase extraction approach for specific capture of quinolones in animal innards prior to UHPLC–Q–Orbitrap HRMS detection - Shumin Lin; Yun-kai Lv; Aixue Zhu; Ming Su; Xiliang Li; Shu-xuan Liang (Food Chemistry, 2024)

No Association of Polycystic Ovary Syndrome with Pancreatic Cancer: A Mendelian Randomization Study - Xueying Gao; Yuteng Wang; Yikun Wang; Ziyi Yang; Xueqi Yan; Shumin Li; Yonghui Jiang; Yimeng Li; Shigang Zhao; Han Zhao; Zi-Jiang Chen (Phenomics, 2024)

The impact of aeration rate on the denitrification performance and microbial community characteristics of the HN-AD bacteria-inoculated MBBR system - Qian Zhang; Chenxi Yang; Shumin Qin; Peng Zhang; Yu Hu; Huacan Tian; Baiying Liu; Haiying Chen; Wei Li (Journal of Water Process Engineering, 2024)

Development and characterization of adhesives constructed by soy protein isolate and tea polyphenols for enhanced tensile strength in plant-protein meat applications - Zixi Xue; Minghao Zhang; Meiquan Wang; Shengnan Wang; Shumin Wang; Peng Wang; Jun Li; He Liu (Food Chemistry, 2024)

Preparation of Ultra-Sensitive flexible temperature sensors with thermal responsive waterborne polyurethane for enhanced temperature sensing performance - Chenguang Kong; Xiaobin Li; Jun Shi; Hangzhou Wang; Cunzhi Li; Youcheng Huang; Shumin Jiang; Kun Wu; Li Yang (Chemical Engineering Journal, 2024)

Morphological Tracing and Functional Identification of Monosynaptic Connections in the Brain: A Comprehensive Guide - Yuanyuan Li; Yuanyuan Fang; Kaiyuan Li; Hongbin Yang; Shumin Duan; Li Sun (Neuroscience Bulletin, 2024)
Behavioral studies play a crucial role in unraveling the mechanisms underlying brain function. Recent advances in optogenetics, neuronal typing and labeling, and circuit tracing have facilitated the dissection of the neural circuitry involved in various important behaviors. The identification of monosynaptic connections, both upstream and downstream of specific neurons, serves as the foundation for understanding complex neural circuits and studying behavioral mechanisms. However, the practical implementation and mechanistic understanding of monosynaptic connection tracing techniques and functional identification remain challenging, particularly for inexperienced researchers. Improper application of these methods and misinterpretation of results can impede experimental progress and lead to erroneous conclusions. In this paper, we present a comprehensive description of the principles, specific operational details, and key steps involved in tracing anterograde and retrograde monosynaptic connections. We outline the process of functionally identifying monosynaptic connections through the integration of optogenetics and electrophysiological techniques, providing practical guidance for researchers.

Impact of Nitrogen Use Efficiency Towards Ammonia-Oxidizing Microbes in Rhizosphere Soil of Intercropped Soybean and Maize - Yuhang Zhang; Runzhi Zhang; Shuchang Zhao; Shumin Li; Lingbo Meng (Journal of Soil Science and Plant Nutrition, 2024)

Protective mechanism of carbon dioxide in pipelines for water containing typical corrosive anions - Shumin Yang; Mei Li; Tuodong Liu; Peizhi Gao; Huajun Zhang; Chao Yin; Yulin Tang (Process Safety and Environmental Protection, 2024)

Occurrence, distribution characteristics and exposure assessment of perchlorate in the environment in China - Diancheng Dou; Ming He; Jinxin Liu; Shumin Xiao; Fu Gao; Wei An; Li Qi (Journal of Hazardous Materials, 2024)

Epimedin B exerts an anti-inflammatory effect by regulating the MAPK/NF-κB/NOD-like receptor signalling pathways - Li Liu; Yayun Zhong; Te Zheng; Jingcheng Zhao; Shumin Ding; Jinpeng Lv; Qian Xu; Yun Zhang (Fish & Shellfish Immunology, 2024)

Development and characterization of Artemisia argyi essential oil-loaded nanoemulsion for sustainable weed control: Enhanced stability, amplified activity, protected non-target - Hong Chen; Jinxin Li; Xinglei Chen; Likun Mei; Shumin Feng; Pengfei Duan; Huixia Cai; Kaili Qu; Jingyi Zhang; Yuhuan Miao; Dahui Liu (Journal of Cleaner Production, 2024)

The metabolic intermediate of sulfonamides alters soil nitrous oxide emissions - Jie Wu; Zhutao Li; Pinshang Xu; Shumin Guo; Kejie Li; Jinyang Wang; Jianwen Zou (European Journal of Soil Biology, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

Reducing oil absorption in pea starch through two-step annealing with varying temperatures - Shumin Xie; Zihan Li; Qingfei Duan; Weijuan Huang; Wei Huang; Yawei Deng; Pei Chen; Fengwei Xie (Food Hydrocolloids, 2024)

Characterization of Organosulfates (OSs) in typical urban areas in Eastern China: Source, Process, and Volatility - Yang Du; Hanxiong Che; Zier Bao; Yiliang Liu; Qing Li; Miao Hu; Jiawei Zhou; Shumin Zhang; Xiaojiang Yao; Quan Shi; Chunmao Chen; Yan Han; et al. (Atmospheric Research, 2024)

Lower soil nitrogen-oxide emissions associated with enhanced denitrification under replacing mineral fertilizer with manure in orchard soils - Pinshang Xu; Zhutao Li; Shumin Guo; Davey L. Jones; Jinyang Wang; Zhaoqiang Han; Jianwen Zou (Science of The Total Environment, 2024)

OcBSA: An NGS-based bulk segregant analysis tool for outcross populations - Lingkui Zhang; Yanfeng Duan; Zewei Zhang; Lei Zhang; Shumin Chen; Chengcheng Cai; Shaoguang Duan; Kang Zhang; Guangcun Li; Feng Cheng (Molecular Plant, 2024)

Potential mitigation of titanium dioxide nanoparticles against 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis through inhibiting the canonical NF-κB pathway - Yanjun Gao; Langzhi He; Shumin Duan; Hasen Bilige; Lizhi Lyu; Zihui Li; Hongbo Wang; Chen Li; Yun Wang (NanoImpact, 2024)

Effect of lactic acid bacteria fermentation on bioactive components of black rice bran (Oryza sativa L.) with different milling fractions - Shumin Lin; Xinxia Zhang; Junren Wang; Ting Li; Li Wang (Food Bioscience, 2024)

Synchronized achieving amount reduction and efficiency increase of lithium salt-type additive by alternating current pulse discharge technology - Shiyou Li; Yulong Zhang; Shumin Wu; Yin Quan; Meiling Wu; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2024)

Application of Multi-Strategy Based Improved DBO Algorithm in Optimal Scheduling of Reservoir Groups - Ji He; Wen Guo; Songlin Wang; Haitao Chen; Xiaoqi Guo; Shumin Li (Water Resources Management, 2024)

Plant polyphenols regulating myoglobin oxidation and color stability in red meat and certain fish: A review - Wenhui Zhu; Menglin Han; Ying Bu; Xuepeng Li; Shumin Yi; Yongxia Xu; Jianrong Li (Critical Reviews in Food Science and Nutrition, 2024)

Characterization of risks and pathogenesis of respiratory diseases caused by rural atmospheric PM2.5 - Ronghua Zhang; Xiaomeng Li; Xuan Li; Qin Zhang; Jiancai Tang; Zhenzhong Liu; Guiqin Song; Li Jiang; Fumo Yang; Jiawei Zhou; Hanxiong Che; Yan Han; et al. (Science of The Total Environment, 2024)

Using machine learning to trace the pollution sources of disinfection by-products precursors compared to receptor models - Yuan Xiao; Shunjun Ma; Shumin Yang; Huan He; Xin He; Cheng Li; Yuheng Feng; Bin Xu; Yulin Tang (Science of The Total Environment, 2024)

Zinc Oxide Nanoparticles Trigger Autophagy in the Human Multiple Myeloma Cell Line RPMI8226: an In Vitro Study - Zonghong Li; Xuewei Yin; Chunyi Lyu; Jingyi Wang; Kui Liu; Siyuan Cui; Shumin Ding; Yingying Wang; Jinxin Wang; Dadong Guo; Ruirong Xu (Biological Trace Element Research, 2024)

In Vitro Virulence Contrast of Seven Genetically Distinct Toxoplasma gondii Isolates After Rejuvenation In Vivo - Haiting Guo; Jie Tan; Yulin He; Shumin Yuan; Ke Jin; Zhongyuan Li (Acta Parasitologica, 2024)

Mechanism of inactivation of Aspergillus flavus spores by dielectric barrier discharge plasma - Yaxin Wang; Mingming Yu; Yanli Xie; Weibin Ma; Shumin Sun; Qian Li; Yuhui Yang; Xiao Li; Hang Jia; Renyong Zhao (Toxicon, 2024)

Regulating pathway for bacterial diversities toward improved ecological benefits of thiencarbazone-methyl·isoxaflutole application: A field experiment - Yonglu Wang; Liyun Zhang; Shumin Zhang; Shiliang Zhu; Fengsong Zhang; Guixiang Zhang; Bihua Duan; Rui Ren; Hongyu Zhang; Meng Han; Yi Xu; Yuyang Li (Journal of Environmental Management, 2024)

Synergetic catalysis of Ni@C@CeO2 for driving ab/desorption of MgH2 at moderate temperature - Zhichao Yu; Xin Liu; Yang Liu; Yuan Li; Zhuohan Zhang; Kangli Chen; Shumin Han (Fuel, 2024)

Diacylglycerol emulsion with different droplet size improves the gelation properties of Nemipterus virgatus myofibrillar protein - Yanan Lv; Honglei Zhao; Yongxia Xu; Shumin Yi; Xuepeng Li; Jianrong Li (Food Chemistry, 2024)

Different responses of Sinorhizobium sp. upon Pb and Zn exposure: Mineralization versus complexation - Peihuan Li; Jiale Chen; Shumin Ying; Nike Chen; Shu Fang; Menglei Ye; Chunhua Zhang; Chonghua Li; Ying Ge (Environmental Pollution, 2024)

Tracking long-term effects of check dams and afforestation on debris flow mitigation in an active gully - Guanyu Zhou; Liqun Lyu; Jun Li; Shumin Lyu; Chao Ma; Yunqi Wang; Yujie Wang; Mengzhen Xu; Zhaoyin Wang (Natural Hazards, 2024)

Research on topological effect of natural small molecule and high–performance antibacterial air filtration application by electrospinning - Zungui Shao; Junjie Xie; Jiaxin Jiang; Ruimin Shen; Zeqian Gui; Haonan Li; Xiang Wang; Wenwang Li; Shumin Guo; Yifang Liu; Gaofeng Zheng (Science of The Total Environment, 2024)

Calculation and utility analysis of lychee life-cycle carbon emissions considering food loss and waste - Guanghai Liu; Zhijing Kuang; Jie Tang; Shumin Kuang; Quan Tian; Yifeng Zou; Qingting Li (Journal of Cleaner Production, 2024)

A low energy-consuming phase change absorbent of MAE/DGM/H2O for CO2 capture - Shumin Hong; Ting Li; Min Xiao; Teerawat Sema; Hongxia Gao; Zhiwu Liang (Chemical Engineering Journal, 2024)

Photoinitiator-grafted polymer coating enable various hydrogels with strong resistance to both drying and swelling - Xiaobin Li; Jun Shi; Chenguang Kong; Cunzhi Li; Hangzhou Wang; Shumin Jiang; Yang Li (Chemical Engineering Journal, 2024)

Atomic ruthenium doping in collaboration with oxygen vacancy engineering boosts the hydrogen evolution reaction by optimizing H absorption - Dong Sui; Ruishen Luo; Shumin Xie; Heng Zhang; Tiantian Ma; Hao Sun; Tong-Tong Jia; Jing Sun; Xingyun Li (Chemical Engineering Journal, 2024)

The covariability between temperature inversions and aerosol vertical distribution over China - Zhongmin Zhu; Hui Li; Shumin Fan; Wenfa Xu; Ruimin Fang; Boming Liu; Wei Gong (Atmospheric Pollution Research, 2024)

Effect of light wavelengths on algal-bacterial symbiotic particles (ABSP): Nitrogen removal, physicochemical properties, community structure - Shumin Wang; Zhongyou Jin; Zhihong Chen; Zheng Zheng; Linling Li; Xiaofan Ding; Chengcai Zhang; Guangjun Lv (Journal of Cleaner Production, 2023)

Crucial role of Mg on phase transformation and stability of Sm–Mg–Ni-based AB2 type hydrogen storage alloy - Yongxi Zhang; Yuan Li; Guanjiu Wu; Chenfeng Fan; Lu Zhang; Shumin Han (Chemical Engineering Journal, 2023)

Realization and Online Optimization for Gliding and Flapping Propulsion of a Manta Ray Robot - Yonghui Cao; Yingzhuo Cao; Shumin Ma; Xinhao Li; Yilin Qu; Yong Cao (Journal of Marine Science and Engineering, 2023)
Currently, the bionic robotic fish is primarily devoted to the bionic appearance of fish and rarely involves the bionic swimming posture. However, biological studies have proved that fish have extraordinary swimming ability, so it is necessary to imitate the swimming posture of fish. This paper introduces a manta ray robot driven by three fin rays, with its pectoral fins being structurally simulated using silicone rubber. According to the manta ray’s integrated gliding and flapping propulsion characteristics, we established a central-pattern-generator-based (CPG-based) biomimetic-motion-control method to realize the manta ray robot’s integrated gliding and flapping propulsion control. We designed an evaluation method of motion–posture similarity for the manta ray robot and optimized the control parameters to enhance the resemblance to the manta ray robot. The experimental results show that the online similarity-optimization method based on particle swarm optimization enhances the resemblance to 86.93%, and its swimming stability is also improved to some extent, which verifies the effectiveness of the optimization method. This study provides a new idea for optimizing motion control of the manta ray robot and realizing environmental affinity.

Removal of Microcystis aeruginosa by manganese activated sodium percarbonate: Performance and role of the in-situ formed MnO2 - Nan Li; Fan Chen; Shunkai Xu; Shumin Zhu; Lingjun Bu; Lin Deng; Zhou Shi; Shiqing Zhou (Chemosphere, 2023)

Accuracy evaluation of ET and its components from three remote sensing ET models and one process based hydrological model using ground measured eddy covariance and sap flow - Xiaojin Li; Yonghui Yang; Xinyao Zhou; Shumin Han; Huilong Li; Yanmin Yang; Xiaohua Hao (Journal of Hydrology, 2023)

Properties and microstructures of golden thread fish myofibrillar proteins gel filled with diacylglycerol emulsion: Effects of emulsifier type and dose - Yanan Lv; Honglei Zhao; Yongxia Xu; Shumin Yi; Xuepeng Li; Jianrong Li (Food Hydrocolloids, 2023)

Role and anti-inflammatory mechanisms of acupuncture and moxibustion therapy on pain relief through NOX-ROS-NLRP3 pathway in CCI rats models - Wang Jinying; Li Keming; Tang Hanqing; Zhang Xuqing; Fatima Muccee; Luo Xuan; Liu Yalin; Song Meiye; Zhang Shumin; Chandrabose Selvaraj; Sher Zaman Safi (Molecular Biology Reports, 2023)

Temporal-spatial Generation of Astrocytes in the Developing Diencephalon - Wentong Hong; Pifang Gong; Xinjie Pan; Zhonggan Ren; Yitong Liu; Guibo Qi; Jun-Liszt Li; Wenzhi Sun; Woo-Ping Ge; Chun-Li Zhang; Shumin Duan; Song Qin (Neuroscience Bulletin, 2023)
Astrocytes are the largest glial population in the mammalian brain. However, we have a minimal understanding of astrocyte development, especially fate specification in different regions of the brain. Through lineage tracing of the progenitors of the third ventricle (3V) wall via in-utero electroporation in the embryonic mouse brain, we show the fate specification and migration pattern of astrocytes derived from radial glia along the 3V wall. Unexpectedly, radial glia located in different regions along the 3V wall of the diencephalon produce distinct cell types: radial glia in the upper region produce astrocytes and those in the lower region produce neurons in the diencephalon. With genetic fate mapping analysis, we reveal that the first population of astrocytes appears along the zona incerta in the diencephalon. Astrogenesis occurs at an early time point in the dorsal region relative to that in the ventral region of the developing diencephalon. With transcriptomic analysis of the region-specific 3V wall and lateral ventricle (LV) wall, we identified cohorts of differentially-expressed genes in the dorsal 3V wall compared to the ventral 3V wall and LV wall that may regulate astrogenesis in the dorsal diencephalon. Together, these results demonstrate that the generation of astrocytes shows a spatiotemporal pattern in the developing mouse diencephalon.

Uncovering the prevalence and drivers of antibiotic resistance genes in soils across different land-use types - Jie Wu; Shumin Guo; Haiyan Lin; Kejie Li; Zhutao Li; Jinyang Wang; William H. Gaze; Jianwen Zou (Journal of Environmental Management, 2023)

Maize/soybean intercrop over time has higher yield stability relative to matched monoculture under different nitrogen-application rates - Xiaodan Liu; Lingbo Meng; Tengjiao Yin; Xuerong Wang; Shu Zhang; Zeyu Cheng; Abiola O. Ogundeji; Shumin Li (Field Crops Research, 2023)

Effect of fertilizer type on antibiotic resistance genes by reshaping the bacterial community and soil properties - Jie Wu; Shumin Guo; Kejie Li; Zhutao Li; Pinshang Xu; Davey L. Jones; Jinyang Wang; Jianwen Zou (Chemosphere, 2023)

Transcriptome analysis provides insights into the mechanism of carapace stripe formation in two closely related Marsupenaeus species - Panpan Wang; Shumin Xie; Xinyang Li; Jiawei Zhu; Ziqi You; Xinlei Zhou; Xinyi Zhou; Binlun Yan; Huan Gao; Chaofan Xing (Frontiers in Marine Science, 2023)
Marsupenaeus japonicus has two types of phenotypic differences that are mainly reflected in the stripe pattern of the carapace. However, the underlying mechanism regulating the stripe patterns is not clear. In the present study, we first observed the composition of pigment cells and detected the contents of different carotenoids in the carapace of M. japonicus . We clearly observed the setae structure on the carapace. There were red pigment cells in the stripe pattern and yellow pigment cells in the other parts. Both red pigment cells and yellow pigment cells showed dendritic morphology. In the carapace, the content of astaxanthin was the highest, significantly ( P < 0.05) higher than that of other carotenoids. Some differentially expressed genes between two pattern types of M. japonicus , may be associated with the body color formation, such as crustacyanin ( CRCN ), apolipoprotein D ( ApoD ), tubulin alpha-1 chain, cuticle protein, and ABC transporter, which were verified by quantitative PCR experiments. The amino acid composition and secondary structure of CRCN A2 , CRCN C1 , and ApoD were significantly different. The results of this study will help to elucidate the molecular mechanism of the differential pattern formation of M. japonicus and provide a reference for further exploration of the formation mechanism of crustacean color.

Insights into the interaction mechanism of acid phosphatase from Lateolabrax japonicus livers and rosmarinic acid using multispectroscopy and molecular docking - Yingchang Li; Yuanyuan Li; Nan Zhao; Danhua Shi; Shumin Yi; Jianrong Li (Food Chemistry, 2023)

Effects of chickpea protein-stabilized Pickering emulsion on the structure and gelling properties of hairtail fish myosin gel - Huinan Wang; Jiaxin Zhang; Yongxia Xu; Hongbo Mi; Shumin Yi; Ruichang Gao; Xuepeng Li; Jianrong Li (Food Chemistry, 2023)

Accumulation characteristics and risk of heavy metals and microbial community composition in bioretention systems: A case study of a university campus - Xiaolong Duan; Shumin Wang; Jiake Li (Ecological Engineering, 2023)

Model-Driven Deep-Learning-Based Underwater Acoustic OTFS Channel Estimation - Yuzhi Zhang; Shumin Zhang; Yang Wang; Qingyuan Liu; Xiangxiang Li (Journal of Marine Science and Engineering, 2023)
Accurate channel estimation is the fundamental requirement for recovering underwater acoustic orthogonal time–frequency space (OTFS) modulation signals. As the Doppler effect in the underwater acoustic channel is much more severe than that in the radio channel, the channel information usually cannot strictly meet the compressed sensing sparsity assumption in the orthogonal matching pursuit channel estimation algorithm. This deviation ultimately leads to a degradation in system performance. This paper proposes a novel approach for OTFS channel estimation in underwater acoustic communications, utilizing a model-driven deep learning technique. Our method incorporates a residual neural network into the OTFS channel estimation process. Specifically, the orthogonal matching pursuit algorithm and denoising convolutional neural network (DnCNN) collaborate to perform channel estimation. The cascaded DnCNN denoises the preliminary channel estimation results generated by the orthogonal matching pursuit algorithm for more accurate OTFS channel estimation results. The use of a lightweight DnCNN network with a single residual block reduces computational complexity while still preserving the accuracy of the neural network. Through extensive evaluations conducted on simulated and experimental underwater acoustic channels, the outcomes demonstrate that our proposed method outperforms traditional threshold-based and orthogonal matching pursuit channel estimation techniques, achieves superior accuracy in channel estimation, and significantly reduces the system’s bit error rate.

Diversity, community structure, and quantity of eukaryotic phytoplankton revealed using 18S rRNA and plastid 16S rRNA genes and pigment markers: a case study of the Pearl River Estuary - Shumin Xu; Guihao Li; Cui He; Yi Huang; Dan Yu; Huiwen Deng; Zhuyin Tong; Yichong Wang; Christine Dupuy; Bangqin Huang; Zhuo Shen; Jie Xu; et al. (Marine Life Science & Technology, 2023)
Understanding consistencies and discrepancies in characterizing diversity and quantity of phytoplankton is essential for better modeling ecosystem change. In this study, eukaryotic phytoplankton in the Pearl River Estuary, South China Sea were investigated using nuclear 18S rRNA and plastid 16S or 23S rRNA genes and pigment analysis. It was found that 18S abundance poorly explained the variations in total chlorophyll a (Chl- a ). However, the ratios of log-transformed 18S abundance to Chl- a in the major phytoplankton groups were generally environment dependent, suggesting that the ratio has potential as an indicator of the physiological state of phytoplankton. The richness of 18S-based operational taxonomic units was positively correlated with the richness of 16S-based amplicon sequence variants of the whole phytoplankton community, but insignificant or weak for individual phytoplankton groups. Overall, the 18S based, rather than the 16S based, community structure had a greater similarity to pigment-based estimations. Relative to the pigment data, the proportion of haptophytes in the 18S dataset, and diatoms and cryptophytes in the 16S dataset, were underestimated. This study highlights that 18S metabarcoding tends to reflect biomass-based community organization of eukaryotic phytoplankton. Because there were lower copy numbers of plastid 16S than 18S per genome, metabarcoding of 16S probably approximates cell abundance-based community organization. Changes in biomass organization of the pigment-based community were sensitive to environmental changes. Taken together, multiple methodologies are recommended to be applied to more accurately profile the diversity and community composition of phytoplankton in natural ecosystems.

Muscle Transcriptome Analysis Reveals Molecular Mechanisms of Superior Growth Performance in Kuruma Shrimp, Marsupenaeus japonicus - Panpan Wang; Fei Yu; Xinyang Li; Shumin Xie; Lei Wang; Jiawei Zhu; Xinlei Zhou; Xinyi Zhou; Binlun Yan; Huan Gao; Chaofan Xing (Fishes, 2023)
During the cultivation of Marsupenaeus japonicus, there are often obvious differences in the growth within the same family under the same food, water quality, and environment, which greatly affects cultivation efficiency. To explore the molecular mechanism of this growth difference, this study used RNA-seq technology to compare the transcriptomes of M. japonicus individuals with significant growth differences from the same family. A total of 1375 differentially expressed genes were identified, of which 1109 were upregulated and 266 were downregulated. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed on the differentially expressed genes, and the results showed that growth-related processes, including chitin metabolism, chitin-binding amino sugar metabolism, and antioxidant processes, including response to oxidative stress, peroxidase activity, antioxidant activity, and peroxidase activity, showed significant differences between the large-size and small-size groups. The expression levels of some differentially expressed genes, such as cuticular protein, low-density lipoprotein receptor, ecdysteroid kinase, myosin heavy chain, and apoptosis inhibitor, were verified by quantitative PCR experiments. One cuticle gene was annotated, and phylogenetic analysis showed that this sequence clustered with the penaeid cuticle genes. This study provides valuable data and a scientific basis for understanding the mechanism of growth differences in M. japonicus at the molecular-genetic level.

Mutagenicity of PM2.5 and Ethnic Susceptibility in Chengdu-Chongqing Economic Circle, China - Shumin Zhang; Qin Zhang; Xiaomeng Li; Ronghua Zhang; Hanxiong Che; Zhenzhong Liu; Dongmei Guo; Fumo Yang; Yang Chen (Science of The Total Environment, 2023)

Ursolic acid promotes microglial polarization toward the M2 phenotype via PPARγ regulation of MMP2 transcription - Yuye Wang; Luying Qiu; Shumin Deng; Fang Liu; Zhiyi He; Mengye Li; Yanzhe Wang (NeuroToxicology, 2023)

Formation characteristics of algal-bacteria granular sludge under low-light environment: From sludge characteristics, extracellular polymeric substances to microbial community - Zhe Liu; Jingwen Wang; Shumin Zhang; Yiwen Hou; Jiaxuan Wang; Min Gao; Xingdu Chen; Aining Zhang; Yongjun Liu; Zhihua Li (Bioresource Technology, 2023)

Exploring the relationship between seasonal variations of land surface temperature and urban morphological factors in complex urban areas - Jiachen Liu; Shumin Zhang; Le Yin; Bin Li; Baolei Zhang (Environmental Science and Pollution Research, 2023)

Antibiotics and antibiotic resistance genes in agricultural soils: A systematic analysis - Jie Wu; Jinyang Wang; Zhutao Li; Shumin Guo; Kejie Li; Pinshang Xu; Yong Sik Ok; Davey L. Jones; Jianwen Zou (Critical Reviews in Environmental Science and Technology, 2023)

Event‐based precipitation characteristics related to cloud‐top temperature during pre‐summer rainy season over south China - Aoqi Zhang; Yilun Chen; Weibiao Li; Shumin Chen (International Journal of Climatology, 2023)
Precipitation exists in the form of event, which means all pixels within the same event have similar atmospheric condition and development experiences. Therefore, using GPM DPR and Himawari‐8 AHI data from 2016 to 2020, we carried out event‐based investigations on precipitations during the pre‐summer rainy season over south China. The identified rain clusters (RCs) were classified into three classes based on the mode of cloud‐top temperature, including those 265 K. The results show that RCs with mode of cloud‐top temperature 265 K contributed less than 10% of the accumulated rainfall amount. They were mainly warm‐cloud shallow precipitations triggered by local convection with low droplet density. Our results suggest that the event‐scale characteristics of precipitation are indicative of the triggers and microphysics of precipitation.

Effects of ultrasound–assisted freezing on the quality of large yellow croaker (Pseudosciaena crocea) subjected to multiple freeze–thaw cycles - Hongyue Li; Lei Wang; Jinxiang Wang; Xuepeng Li; Jianrong Li; Fangchao Cui; Shumin Yi; Yongxia Xu; Wenhui Zhu; Hongbo Mi (Food Chemistry, 2023)

Prediction of the freshness of horse mackerel (Trachurus japonicus) using E-nose, E-tongue, and colorimeter based on biochemical indexes analyzed during frozen storage of whole fish - Hongyue Li; Yang Wang; Jiaxin Zhang; Xuepeng Li; Jinxiang Wang; Shumin Yi; Wenhui Zhu; Yongxia Xu; Jianrong Li (Food Chemistry, 2023)

A hybrid method for optimization of frame structures with good constructability - An Xu; Shumin Li; Jiyang Fu; Anil Misra; Ruohong Zhao (Engineering Structures, 2023)

Catalytic effect of bamboo-like carbon nanotubes loaded with NiFe nanoparticles on hydrogen storage properties of MgH2 - Yaokun Fu; Zhichao Yu; Sanyang Guo; Yuan Li; Qiuming Peng; Lu Zhang; Shikui Wu; Shumin Han (Chemical Engineering Journal, 2023)

Mixing-layer depth-based backwards trajectory analysis of the sources of high O3 concentrations at the Wutaishan station, North China - Shiming Yan; Xingai Gao; Kunning Pei; Hongping Sun; Yan Wang; Fengsheng Zhang; Ying Li; Shumin Wang; Ling Chen; Jian Dong; Feihong Yang (Atmospheric Pollution Research, 2023)

Migration and diffusion of unsteady-state flow of volatile organic compounds on activated carbon adsorption beds under reverse ventilation - Tao Liu; Ning Qiang; Jiao He; Haichao Miao; Zhaohai Li; Yiqi Cao; Tianzhe Shi; Shumin Chen (Chemosphere, 2023)

Research progress of ochratoxin a bio-detoxification - Fred Mwabulili; Yanli Xie; Qian Li; Shumin Sun; Yuhui Yang; Weibin Ma (Toxicon, 2023)

Composite films with properties improved by increasing the compatibility of sodium caseinate and zein in a heated 60% ethanol solvent - Shumin Wang; Han Chen; Yi Tong; Yi Li; Jijun Zhang; Chong Chen; Fazheng Ren; Caiyun Hou; Pengjie Wang (Food Hydrocolloids, 2023)

A long-life aqueous Zn battery enabled by simultaneous suppressing cathode dissolution and Zn dendrites via a novel water-in-deep eutectic solvent electrolyte - Wenfeng Wang; Ruyue Li; Zeang Duan; Jiajin Zhao; Yadi Qi; Qiubo Guo; Qiuming Peng; Desong Wang; Shumin Han; Lu Zhang (Chemical Engineering Journal, 2023)

Experimental study on the effect of cold soaking with liquid nitrogen on the coal chemical and microstructural characteristics - Shumin Liu; Xuelong Li (Environmental Science and Pollution Research, 2022)

Maize/soybean intercropping improves stability of soil aggregates driven by arbuscular mycorrhizal fungi in a black soil of northeast China - Shu Zhang; Lingbo Meng; Jian Hou; Xiaodan Liu; Abiola O. Ogundeji; Zeyu Cheng; Tengjiao Yin; Nicholas Clarke; Baozhong Hu; Shumin Li (Plant and Soil, 2022)

A stable method for Agrobacterium-mediated transformation of Mentha piperita and Mentha canadensis using internodal explants - Xu Yu; Zequn Chen; Shumin Li; Xiwu Qi; Hailing Fang; Yang Bai; Li Li; Dongmei Liu; Qun Liu; Weilin Li; Chengyuan Liang (In Vitro Cellular & Developmental Biology - Plant, 2022)

Damage assessment for tropical cyclones landing in Guangdong Province of China by using a projection pursuit dynamic cluster model - Chaoyong Tu; Shumin Chen; Zhongkuo Zhao; Weibiao Li; Changjian Ni (Natural Hazards, 2022)

Pathological Networks Involving Dysmorphic Neurons in Type II Focal Cortical Dysplasia - Yijie Shao; Qianqian Ge; Jiachao Yang; Mi Wang; Yu Zhou; Jin-Xin Guo; Mengyue Zhu; Jiachen Shi; Yiqi Hu; Li Shen; Zhong Chen; Xiao-Ming Li; et al. (Neuroscience Bulletin, 2022)

Interferon-γ enhances the immunosuppressive ability of canine bone marrow-derived mesenchymal stem cells by activating the TLR3-dependent IDO/kynurenine pathway - Jiaqiang Deng; Danting Li; Xiaoya Huang; Weiyao Li; Fangfang Zhao; Congwei Gu; Liuhong Shen; Suizhong Cao; Zhihua Ren; Zhicai Zuo; Junliang Deng; Shumin Yu (Molecular Biology Reports, 2022)

First report of Colletotrichum queenslandicum causing leaf anthracnose on Dracaena cambodiana in China - Shumin Wang; Meijiao Hu; Xiangxiang Qu; Jinyu Yang; Zhaoyin Gao; Shuming Wang; Zhiqiang Liu; Min Li (Journal of General Plant Pathology, 2022)

Enhanced Intramuscular Bioavailability of Cannabidiol Using Nanocrystals: Formulation, In Vitro Appraisal, and Pharmacokinetics - Xinzhen Fu; Shiji Xu; Zhi Li; Kun Chen; Huaying Fan; Yu Wang; Zeping Xie; Lijuan Kou; Shumin Zhang (AAPS PharmSciTech, 2022)

Comparison of the characterization of allergenic protein 3 (Pla a3) released from Platanus pollen grains collected in Shanghai during the spring of 2019 and 2020 - Xingzi Wang; Shumin Zhou; Senlin Lu; Lu Zhang; Teng Ma; Xinchun Liu; Wei Zhang; Shuijun Li; Kai Xiao; Weqian Wang; Qingyue Wang (Aerobiologia, 2022)

Shifting from homogeneous to heterogeneous surfaces in estimating terrestrial evapotranspiration: Review and perspectives - Yuanbo Liu; Guoyu Qiu; Hongsheng Zhang; Yonghui Yang; Yinsheng Zhang; Quan Wang; Wenzhi Zhao; Li Jia; Xibin Ji; Yujiu Xiong; Chunhua Yan; Ning Ma; et al. (Science China Earth Sciences, 2022)

Northward Shift in Landfall Locations of Tropical Cyclones over the Western North Pacific during the Last Four Decades - Ting Chen; Shumin Chen; Mingsen Zhou; Chaoyong Tu; Aoqi Zhang; Yilun Chen; Weibiao Li (Advances in Atmospheric Sciences, 2022)

Influence of water vapor distribution on the simulated track of Typhoon Hato (2017) - Jiaxin Chen; Chuying Mai; Mingsen Zhou; Shumin Chen; Weibiao Li; Rong Fang; Zhongkuo Zhao (Natural Hazards, 2021)
Predicting tropical cyclone (TCs) tracks is a primary concern in TC forecasting. Some TCs appear to move in a direction favorable for their development, beyond the influence of the steering flow. Thus, we hypothesize that TCs move toward regions with high water-vapor content in the lower atmosphere. In this study, four numerical experiments, including a control experiment and three sensitivity experiments, were performed using the Weather Research and Forecasting Model, to analyze the relationship between water vapor distribution and the track of Severe Typhoon Hato (2017). Observations validated the features reproduced in the control experiment. The sensitivity experiments were conducted to explore variations in the TC track under different water vapor environments. Results indicate that the horizontal distribution of water-vapor content exerted a greater impact on the TC track than the steering flow when both factors were significant. Further analysis revealed that the TC’s movement vector was between the direction of the steering flow and the direction toward the peak of vorticity increasing area. The peaks of vorticity increasing area were close to the peaks of water vapor increasing area, which also proved the effect of water vapor distribution on the TC track. These results are expected to improve TC track analysis and forecasting.

Suppressed Thermocline Mixing in the Center of Anticyclonic Eddy in the North South China Sea - Yongfeng Qi; Huabin Mao; Xia Wang; Linhui Yu; Shumin Lian; Xianpeng Li; Xiaodong Shang (Journal of Marine Science and Engineering, 2021)
Direct microstructure observations and fine-scale measurements of an anticyclonic mesoscale eddy were conducted in the northern South China Sea in July 2020. An important finding was that suppressed turbulent mixing in the thermocline existed at the center of the eddy, with an averaged diapycnal diffusivity at least threefold smaller than the peripheral diffusivity. Despite the strong background shear and significant wave–mean flow interactions, the results indicated that the lack of internal wave energy in the corresponding neap tide period during measurement of the eddy’s center was the main reason for the suppressed turbulent mixing in the thermocline. The applicability of the fine-scale parameterization method in the presence of significant wave–mean flow interactions in a mesoscale eddy was evaluated. Overprediction via fine-scale parameterization occurred in the center of the eddy, where the internal waves were inactive; however, the parameterization results were consistent with microstructure observations along the eddy’s periphery, where active internal waves existed. This indicates that the strong background shear and wave–mean flow interactions affected by the mesoscale eddy were not the main contributing factors that affected the applicability of fine-scale parameterization in the northern South China Sea. Instead, our results showed that the activity of internal waves is the most important consideration.

Experimental Study on Temperature Response of Different Ranks of Coal to Liquid Nitrogen Soaking - Shumin Liu; Xuelong Li; Dengke Wang; Dongming Zhang (Natural Resources Research, 2021)

Satellite Observations of Reflectivity Maxima above the Freezing Level Induced by Terrain - Aoqi Zhang; Weibiao Li; Shumin Chen; Yilun Chen; Yunfei Fu (Advances in Atmospheric Sciences, 2021)

Morphological Characteristics of Precipitation Areas over the Tibetan Plateau Measured by TRMM PR - Yilun Chen; Aoqi Zhang; Yunfei Fu; Shumin Chen; Weibiao Li (Advances in Atmospheric Sciences, 2021)

Preliminary study on relationships among nutritional risk, serum prealbumin, and peripheral blood T cell subsets in patients with severe COVID-19 - Yanli Li; Yanbo Sun; Jing He; Peng Zhao; Pengju Luo; Jinsong Bai; Weiming Li; Shumin Li; Yueying Lin; Yunyun Cen (Infectious Diseases, 2021)

Uncovering the mysterious identity of Taisui—an old Chinese folk legend - Erwei Li; Jinwei Ren; Qian Chen; Hanxing Zhang; Bin Lin; Hui Zhang; Shumin Zhang; Xiaoling Zhang; Lei Cai; Xingzhong Liu (Science China Life Sciences, 2020)

Numerical simulation of the coal temperature field evolution under the liquid nitrogen cold soaking - Shumin Liu; Xuelong Li; Dengke Wang (Arabian Journal of Geosciences, 2020)

Anxiolytic Effect of Increased NREM Sleep after Acute Social Defeat Stress in Mice - Xiang Feng; Hui-Ying Zhao; Yu-Jin Shao; Hui-Fang Lou; Li-Ya Zhu; Shumin Duan; Yan-Qin Yu (Neuroscience Bulletin, 2020)
Social defeat stress (SDS) plays a major role in the pathogenesis of psychiatric disorders like anxiety and depression. Sleep is generally considered to involve recovery of the brain from prior experience during wakefulness and is altered after acute SDS. However, the effect of acute SDS on sleep/wake behavior in mice varies between studies. In addition, whether sleep changes in response to stress contribute to anxiety is not well established. Here, we first investigated the effects of acute SDS on sleep/wake states in the active period in mice. Our results showed that total sleep time (time in rapid eye-movement [REM] and non-REM [NREM] sleep) increased in the active period after acute SDS. NREM sleep increased mainly during the first 3 h after SDS, while REM sleep increased at a later time. Then, we demonstrated that the increased NREM sleep had an anxiolytic benefit in acute SDS. Mice deprived of sleep for 1 h or 3 h after acute SDS remained in a highly anxious state, while in mice with ad libitum sleep the anxiety rapidly faded away. Altogether, our findings suggest an anxiolytic effect of NREM sleep, and indicate a potential therapeutic strategy for anxiety.

Mechanical and Acoustic Emission Characteristics of Coal at Temperature Impact - Shumin Liu; Xuelong Li; Dengke Wang; Mingyang Wu; Guangzhi Yin; Minghui Li (Natural Resources Research, 2020)

microRNA-499a promotes the progression and chemoresistance of cervical cancer cells by targeting SOX6 - Yibing Chen; Yucen Song; Yanjun Mi; Huan Jin; Jun Cao; Haolong Li; Liping Han; Ting Huang; Xiaofei Zhang; Shumin Ren; Qian Ma; Zhengzhi Zou (Apoptosis, 2020)

Experimental Study on the Microstructure Evolution Laws in Coal Seam Affected by Temperature Impact - Shumin Liu; Dengke Wang; Guangzhi Yin; Minghui Li; Xuelong Li (Rock Mechanics and Rock Engineering, 2020)

Preparation and Flavor Characteristics of Alaska Pollock Frame Seasoning Powder by Solid-Phase Maillard Reaction - Hongwei Luan; Wenhui Zhu; Yue Li; Ying Bu; Xuepeng Li; Yongxia Xu; Shumin Yi; Jianrong Li (Journal of Aquatic Food Product Technology, 2020)

Penicindopene A, a new indole diterpene from the deep-sea fungus Penicillium sp. YPCMAC1 - Lijun Liu; Wei Xu; Shumin Li; Mengying Chen; Yongjun Cheng; Wangjun Yuan; Zhongbin Cheng; Qin Li (Natural Product Research, 2019)

Brain-wide Mapping of Mono-synaptic Afferents to Different Cell Types in the Laterodorsal Tegmentum - Xiaomeng Wang; Hongbin Yang; Libiao Pan; Sijia Hao; Xiaotong Wu; Li Zhan; Yijun Liu; Fan Meng; Huifang Lou; Ying Shen; Shumin Duan; Hao Wang (Neuroscience Bulletin, 2019)

MaMPK2 enhances MabZIP93-mediated transcriptional activation of cell wall modifying genes during banana fruit ripening - Chaojie Wu; Wei Shan; Shumin Liang; Lisha Zhu; Yufan Guo; Jianye Chen; Wangjin Lu; Qianfeng Li; Xinguo Su; Jianfei Kuang (Plant Molecular Biology, 2019)

Targeting gut microbiota as a possible therapy for mastitis - Xiaoyu Hu; Shumin Li; Yunhe Fu; Naisheng Zhang (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Associations of gestational and the first year of life exposure to ambient air pollution with childhood eczema in Hubei, China - Shumin Deng; Danqin Huang; Wei Wang; Hong Yan; Shiyue Li; Hao Xiang (Environmental Science and Pollution Research, 2019)

Adsorption performance and mechanisms of Pb(II), Cd(II), and Mn(II) removal by a β-cyclodextrin derivative - Mengjiao Zhang; Liyun Zhu; Changhua He; Xiaojun Xu; Zhengyang Duan; Shuli Liu; Mingyao Song; Shumin Song; Jiemei Shi; Yu’e Li; Guangzhu Cao (Environmental Science and Pollution Research, 2019)

Atmospheric Response to Mesoscale Ocean Eddies over the South China Sea - Haoya Liu; Weibiao Li; Shumin Chen; Rong Fang; Zhuo Li (Advances in Atmospheric Sciences, 2018)

The Sesuvium portulacastrum Plasma Membrane Na+/H+ Antiporter SpSOS1 Complemented the Salt Sensitivity of Transgenic Arabidopsis sos1 Mutant Plants - Yang Zhou; Xiaochang Yin; Shumin Wan; Yanping Hu; Qing Xie; Ruimei Li; Baibi Zhu; Shaoping Fu; Jianchun Guo; Xingyu Jiang (Plant Molecular Biology Reporter, 2018)

T follicular regulatory cells infiltrate the human airways during the onset of acute respiratory distress syndrome and regulate the development of B regulatory cells - Hongqiang Li; Runv Zhou; Chunmei Wang; Yusheng Li; Guizhen Zheng; Sen Jiang; Tiancao Dong; Jianwen Bai; Shumin Xu (Immunologic Research, 2018)

Variations in High-frequency Oscillations of Tropical Cyclones over the Western North Pacific - Shumin Chen; Weibiao Li; Zhiping Wen; Mingsen Zhou; Youyu Lu; Yu-Kun Qian; Haoya Liu; Rong Fang (Advances in Atmospheric Sciences, 2018)

Macroautophagy occurs in distal TMV-uninfected root tip tissue of tomato taking place systemic PCD - Shumin Zhou; Qiang Hong; Yang Li; Qi Li; Ruisha Li; Hongli Zhang; Mao Wang; Xiaojun Yuan (Protoplasma, 2018)

Human rotavirus strain Wa downregulates NHE1 and NHE6 expressions in rotavirus-infected Caco-2 cells - Honglang Chen; Lijun Song; Guixian Li; Wenfeng Chen; Shumin Zhao; Ruoxia Zhou; Xiaoying Shi; Zhenying Peng; Wenchang Zhao (Virus Genes, 2017)

EGCG protects against homocysteine-induced human umbilical vein endothelial cells apoptosis by modulating mitochondrial-dependent apoptotic signaling and PI3K/Akt/eNOS signaling pathways - Shumin Liu; Zhengwu Sun; Peng Chu; Hailong Li; Anil Ahsan; Ziru Zhou; Zonghui Zhang; Bin Sun; Jingjun Wu; Yalin Xi; Guozhu Han; Yuan Lin; et al. (Apoptosis, 2017)

PST ha5a23, a candidate effector from the obligate biotrophic pathogen P uccinia striiformis f. sp. tritici , is involved in plant defense suppression and rust pathogenicity - Yulin Cheng; Kuan Wu; Juanni Yao; Shumin Li; Xiaojie Wang; Lili Huang; Zhensheng Kang (Environmental Microbiology, 2017)
Summary During the infection of host plants, pathogens can deliver virulence‐associated ‘effector’ proteins to promote plant susceptibility. However, little is known about effector function in the obligate biotrophic pathogen Puccinia striiformis f. sp. tritici ( Pst ) that is an important fungal pathogen in wheat production worldwide. Here, they report their findings on an in planta highly induced candidate effector from Pst , PSTha5a23. The PSTha5a23 gene is unique to Pst and shows a low level of intra‐species polymorphism. It has a functional N‐terminal signal peptide and is translocated to the host cytoplasm after infection. Overexpression of PSTha5a23 in Nicotiana benthamiana was found to suppress the programmed cell death triggered by BAX, PAMP‐INF1 and two resistance‐related mitogen‐activated protein kinases (MKK1 and NPK1). Overexpression of PSTha5a23 in wheat also suppressed pattern‐triggered immunity (PTI)‐associated callose deposition. In addition, silencing of PSTha5a23 did not change Pst virulence phenotypes; however, overexpression of PSTha5a23 significantly enhanced Pst virulence in wheat. These results indicate that the Pst candidate effector PSTha5a23 plays an important role in plant defense suppression and rust pathogenicity, and also highlight the utility of gene overexpression in plants as a tool for studying effectors from obligate biotrophic pathogens.

Chondroitin sulfate/dermatan sulfate sulfatases from mammals and bacteria - Shumin Wang; Kazuyuki Sugahara; Fuchuan Li (Glycoconjugate Journal, 2016)

Degradation of carbamazepine by UV/chlorine advanced oxidation process and formation of disinfection by-products - Shiqing Zhou; Ying Xia; Ting Li; Tian Yao; Zhou Shi; Shumin Zhu; Naiyun Gao (Environmental Science and Pollution Research, 2016)

SZC017, a novel oleanolic acid derivative, induces apoptosis and autophagy in human breast cancer cells - Lei Gao; Yan Wang; Zhen Xu; Xiaorui Li; Jingjun Wu; Shumin Liu; Peng Chu; Zhengwu Sun; Bin Sun; Yuan Lin; Jinyong Peng; Guozhu Han; et al. (Apoptosis, 2015)

Identification and analysis of high-frequency oscillations in the eyewalls of tropical cyclones - Shumin Chen; Youyu Lu; Weibiao Li; Zhiping Wen (Advances in Atmospheric Sciences, 2015)

Effects of Traditional Chinese Medicine Fu Zheng Decoction on the Immunological Function and Clinical Prognosis of the Elderly Patients with Pneumonia - Hongqiang Li; Shumin Xu; Tingting Cheng; Lunxian Tang; Jianwen Bai; Minjia Lin (Cell Biochemistry and Biophysics, 2015)

Thermal effect of intrusive rock on hydrocarbon generation from organic matter - Min Wang; Shuangfang Lu; Shumin Chen; Jianzhong Li; Haitao Xue; Xiaozhi WU; Guohui Chen; Man Zheng; Shiguang Zhang; Wenbiao Huang (Arabian Journal of Geosciences, 2015)

The Adhesion AND Growth of Both the Human Primary Gingival Epithelial Cells and Streptococcus Mutans on Micro-Arc Oxidized Titanium - Jiangning Lv; Hongwei Li; Ying Mu; ShuMin Wang; Jing Sun; Jun Jiang; Ping Ding; Baolin Liu (Cell Biochemistry and Biophysics, 2014)

Antimicrobial effect and membrane-active mechanism of tea polyphenols against Serratia marcescens - Shumin Yi; Wei Wang; Fengling Bai; Junli Zhu; Jianrong Li; Xuepeng Li; Yongxia Xu; Tong Sun; Yutang He (World Journal of Microbiology and Biotechnology, 2014)

Subaquatic volcanic eruptions in continental facies and their influence on high quality source rocks shown by the volcanic rocks of a faulted depression in Northeast China - XuanLong Shan; JiYan Li; ShuMin Chen; QingChang Ran; GuiBiao Chen; Chao Liu (Science China Earth Sciences, 2013)

Impacts of sea spray on the boundary layer structure of Typhoon Imbudo - Jie Tang; Weibiao Li; Shumin Chen; Lei Wang (Acta Oceanologica Sinica, 2013)

Differences of DNA methylation profiles between monozygotic twins’ blood samples - Chengtao Li; Shumin Zhao; Na Zhang; Suhua Zhang; Yiping Hou (Molecular Biology Reports, 2013)

Distribution patterns of appendicularians and copepods and their relationship on the northwest continental shelf of South China Sea during summer - Kaizhi Li; Jianqiang Yin; Liangmin Huang; Shumin Lian; Jianlin Zhang (Acta Oceanologica Sinica, 2012)

Genetic polymorphisms of 12 X-STR for forensic purposes in Shanghai Han population from China - Suhua Zhang; Shumin Zhao; Ruxin Zhu; Chengtao Li (Molecular Biology Reports, 2012)

Selection of 29 highly informative InDel markers for human identification and paternity analysis in Chinese Han population by the SNPlex genotyping system - Chengtao Li; Suhua Zhang; Li Li; Jingzhong Chen; Yan Liu; Shumin zhao (Molecular Biology Reports, 2012)

Calcium ameliorates obesity induced by high-fat diet and its potential correlation with p38 MAPK pathway - Chao Sun; Li Wang; Jun Yan; Shumin Liu (Molecular Biology Reports, 2012)

Fyn Polymorphisms are Associated with Distinct Personality Traits in Healthy Chinese-Han Subjects - Jingying Li; Huan Ma; Shumin Deng; Lijuan Wu; Yinglin Huang; Gang Zhu (Journal of Molecular Neuroscience, 2011)

Association of adiponectin gene polymorphisms with the risk of ischemic stroke in a Chinese Han population - Fang Liu; Zhiyi He; Shumin Deng; Hui Zhang; Nan Li; Jialiang Xu (Molecular Biology Reports, 2011)

Association of Apolipoprotein M Gene Polymorphisms with Ischemic Stroke in a Han Chinese Population - Dongxue Zhao; Zhiyi He; Xue Qin; Lei Li; Fang Liu; Shumin Deng (Journal of Molecular Neuroscience, 2011)

Cloning and characterization of class 1 and class 2 insulin-like growth factor-I mRNA in Songliao black pig - Shuqi Xiao; Shuang Li; Jiabao Zhang; Shumin Zhang; Lisheng Dai; Yonghua Bao; Ning Jiang; Yan Gao; Zhongli Zhao; Delin Mo; Yaosheng Chen; Zhihui Zhao (Molecular Biology Reports, 2009)

Decreased surfactant protein B expression in mice derived completely from embryonic stem cells - Shumin Gao; Xiaohui Wen; Rongrong Yang; Keqian Di; Jun Tong; Xiangyun Li (In Vitro Cellular & Developmental Biology - Animal, 2008)